Constructing a Dynamic Material Perspective of Natural Medicines through Inquiry-Based Experiments: A Case Study of Analyzing Pre- and Post-Processing Components of Panax ginseng and Panax quinquefolius by UPLC - Lv, Qinglin; Zhang, Zhubin; Ye, Feng (Journal of Educational Research and Policies, 2026)
The primary objective of the Natural Medicinal Chemistry experiment course is to help students establish a systematic understanding of the “material basis—bioactive function” relationship. However, traditional teaching has long been plagued by the issues of “emphasizing theory over techniques” and “focusing on results while neglecting processes,” making it difficult for students to develop transferable complex problem-solving skills. Guided by constructivist theory, this study designed an inquiry-based experimental teaching method for undergraduate students majoring in traditional Chinese medicine-related disciplines. The method integrates chromatography-spectroscopy techniques as the main framework, covering herbal pretreatment, isolation and purification of active components, structural identification, and quantitative analysis. Teaching effectiveness was evaluated through exploratory case studies. The results demonstrate that the application of chromatography-spectroscopy technology not only enhances students’ technical operational skills but also fosters the formation of a trinity material perspective of “holistic view-dynamic view-systematic view” in Chinese materia medica and natural medicines.